Komisi Pemberantasan Korupsi Menjadi Objek Hak Angket Dewan Perwakilan Rakyat (Analisis Yuridis Terhadap Putusan Mahkamah Konstitusi Nomor 36/PUU-XV/2017 Dan Undang-Undang MD3) - Nurlette, Paman (Faculty of Law, Universitas Pattimura, 2020)
The style of building our constitutional legal system today is very varied, it has implications for the shifting functions and rights of the State organs including the State organs of the Republic of Indonesia House of Representatives. To understand the conception of the functions and rights of the organs of the Republic of Indonesia Representative Council (DPR RI), it is seen as two sides of a coin (two sides of one coin). The DPR RI's inquiry right is a supervision that must be carried out on policies implemented by the executive. The KPK is an organ that is within the executive family, because it carries out investigations, investigations and prosecutions of corruption cases, such as those carried out by the Prosecutors' Office and the Police. Thus if the KPK is referred to as part of the judiciary. The task of investigation, investigation and prosecution is the task of the executive, not the legislative and judiciary. In addition, the KPK has been an institution that uses the State budget, so it should be overseen by the DPR. if the DPR cannot exercise the right to question the KPK on the grounds of independence. The reason is, it is not right to refuse the right to question the KPK. With the decision of the Constitutional Court (MK) in the main essence of the decision which positions the KPK in institutions that are in the realm of power, the executive for carrying out the task of investigation, investigation and prosecution in corruption, which is actually the same as the authority of the police and prosecutors. The KPK is a state institution that is within the executive power cluster, so the KPK can be the object of using the DPR's questionnaire right as the people's representative who carries out the supervisory function. But the use of the questionnaire right by the DPR cannot be applied in the case that the KPK is carrying out its investigative, investigative and prosecution tasks. This means that the KPK cannot be carried out while the KPK is carrying out its duties.